2004
DOI: 10.1097/00041327-200406000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Visual Manifestations of Visible and Buried Optic Disc Drusen

Abstract: Among 92 eyes with optic disc drusen, only slightly more than 50% produced visual symptoms. Fewer than 50% of drusen were visible ophthalmoscopically. Buried optic disc drusen identified by ultrasound had a significantly lower frequency of associated visual field defects than did visible optic disc drusen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 14 publications
3
81
0
4
Order By: Relevance
“…These findings are similar to other previously published studies that identified that visual field is often affected when exposed ODD are present. 7,10,24,25 However, it is against our expected hypothesis that eyes with ED without a history of papilloedema had 3.86 dB worse Humphrey visual field (HVF) mean MD compared with rPAP-ED (−9.88 vs. −6.02 dB), as we originally thought the combination of both conditions (cODD-rPAP) might lead to a worse visual outcome than either condition alone.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…These findings are similar to other previously published studies that identified that visual field is often affected when exposed ODD are present. 7,10,24,25 However, it is against our expected hypothesis that eyes with ED without a history of papilloedema had 3.86 dB worse Humphrey visual field (HVF) mean MD compared with rPAP-ED (−9.88 vs. −6.02 dB), as we originally thought the combination of both conditions (cODD-rPAP) might lead to a worse visual outcome than either condition alone.…”
Section: Discussionmentioning
confidence: 87%
“…ODD by themselves are associated with visual field deficits in 70% of affected individuals. 10,24,25 ODD tend to evolve over time from being buried to becoming exposed in the setting of optic atrophy and reduction of the retinal nerve fibre layer (RNFL) thickness. 25 Worse visual field deficits are associated with exposed drusen as compared with buried drusen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though patients with buried optic disc drusen have not been well characterised, a review of patients with the condition suggests that clinical symptoms correlate to visibility of the drusen [16]. Concerns of deteriorating vision in the child prompted serial assessments until the time when drusen was visibly confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be due to the fact that the drusen visible with oblique illumination identified by Mustonen [20] were probably hidden but shallow drusen, which we categorized as hidden drusen. Wilkins and Pomeranz [22] reported 42% of visible ODD (33/79 ODD). The evolution of ODD has proved to be a dynamic process, which begins as deep or hidden drusen in childhood and later on, from the second decade of life, become more superficial [1,8,23].…”
Section: Discussionmentioning
confidence: 99%